Intimate partner violence policies - Gatlin, Leah E. (Handbook of forensic social work, 2024)
The chapter begins by discussing the definition and context of intimate partner violence (IPV). This forms the foundation for reviewing the three primary IPV policy goals: harm prevention and crime deterrent, benefit to victims, and IPV service coordination. Next, the chapter discusses important IPV policy types, including mandatory reporting, civil protection orders, and laws governing arrests. A history of IPV policy development follows this overview focusing on three foundational IPV policies: the Family Violence Prevention and Services Act, Victims of Crime Act, and Violence Against Women Act. Next, the chapter highlights populations with unique IPV vulnerabilities, including people with disabilities, older women, immigrant women, transgender women, and gay, lesbian, and bisexual people. Finally, the chapter closes with a discussion of IPV policy framed within social work ethical values.